Effects of glossopharyngeal pistoning for lung insufflation in elite swimmers - Nygren-Bonnier, M.; Gullstrand, L.; Klefbeck, B.; Lindholm, P. (Medicine & Science in Sports & Exercise, 2007)
Purpose: To investigate whether sessions of glossopharyngeal pistoning (GP) to lung volumes exceeding maximum inspiratory capacity in a group of extremely well-trained elite swimmers would affect maximum lung volumes and buoyancies.